A case study of a selected e-commerce office in Metro Manila in relation to employee productivity - Rojas, Patricia Louise C.
Through the decades, workplaces have drastically changed in terms of the nature of work conducted within it and its demand for space. Along with the changes in the workplace brought about by technology are the changes in business platforms as well. E-commerce- also known as online retail-refers to buying and selling of goods and services primarily conducted through the internet (Alarilla, 2006). With this new business model, this study examined the spatial conditions of a selected e-commerce office located in Metro Manila, focusing on their effects on the productivity of its employees. The study made use of the random sampling method in selecting 30 employees in the nine departments of the company as respondents of the survey questionnaire. A site observation and documentation, along with a supplementary semi-structured interview with the company's key informant were also conducted. Data gathering was completed in three weeks time. Findings of the study revolved around the identification and description of the spatial conditions of the space that have a substantial effect on the productivity of the employees. It was concluded through the results that these spatial conditions, specifically the spatial programming and layout space were efficiently managed in the selected office space. Additionally, issues with overcrowding, clutter, and noise surfaced from the results of the study. Essentially, the office space was deemed by the employees to have a substantial effect on their productivity. Future studies may choose to acquire a larger sample size in order to derive a larger range of responses. Also, it was recommended to study other e-commerce office spaces in order to compare and further validate the results derived from this study.